The Gender Pay Gap and It’s Impact on Women’s Economic Empowerment in Indonesia - Ma’arif, Ayuningtyas (AIBPM Publisher, 2023)
The gender pay gap is a long-term problem that can be caused by a variety of factors. Indonesia is one of the countries with a high gender pay gap. This also results in the low contribution of women in society in economic, political, and social aspects. This study aims to analyze and discuss the gender wage gap and women's empowerment in Indonesia and the impact of the gender wage gap on women's empowerment. The method used in this research is a qualitative approach using secondary data from BPS, ILO, and other appropriate data. The results of this study show that the inter-gender wage gap in Indonesia tends to fluctuate, women's empowerment is still lacking seen from the role of women in society, and there is a strong relationship between the inter- gender wage gap and the condition of women's empowerment.